Effect of Goat Manure and Super Natural Nutrition (SNN) Organic Fertilizer on the Growth of Local Vaietas (Theobroma cacao L.) - Yulianus Tibe (Universitas 17 Agustus 1945 Samarinda, 2019)
Plant Seeds. The aim of the study was to determine the effect of goat manure and the dose of Super Natural Nutrition Organic Fertilizer and its interaction on the growth of local varieties of cacao (Theobroma cacao L.) seeds.The research design used was a Completely Randomized Design (CRD) in factorial 4 x 4, and repeated 4 times, consisting of 2 research factors. The first factor is goat manure (P). The second factor is Liquid Organic Fertilizer Super Natural Nutrition (K).The results showed that the treatment of goat manure (P) had no significant effect on the diameter of cocoa seedlings 60 days after planting (HST), the number of cacao seedlings aged 30, 60 HST and very significant effect on the height of cocoa seedlings aged 30, 60, 90 and 120 HST, diameter of cacao seedlings aged 30, 90, 120 HST, number of cacao seedlings aged 90 and 120 HST and root length. The treatment of good manure is p3 (goat manure 60 g / polybag). The highest cacao seedling height is 41.45 cm and the lowest is p0 (without goat manure): 30.67 cm, for the highest diameter of cocoa seedlings 0.071 cm and the lowest treatment k0 (without goat manure): 0.058 cm and leaves at most 20 pieces, and the number of leaves is a little p0 (without goat manure) 9 pieces. The longest root of cocoa seedlings is 15.06 cm and the shortest root length with treatment k0 (without goat manure): 13 cm.The treatment of Super Natural Nutrition liquid organic fertilizer had no significant effect on the number of cocoa seedlings aged 60, 120 HST and the root length of cocoa seedlings aged 120 days after planting, but significantly affected the height of cocoa seedlings, cocoa seedling stem diameter of 120 HST and very the actual height of the plant, the diameter of the cacao seedlings aged 30, 60, 90 HST, the number of cacao seedlings aged 30, 90 HST. The best treatment for Super Natural Nutrition organic liquid fertilizer for the highest cocoa seed height is (k3); 5 ml of POC SNN / l water is 35, 69 cm and the lowest is k0 (without POC SNN) which is 34.80 cm.